The Disproportionate Sales Tax Compliance Burden on Small- and Medium-Sized Online Businesses After Wayfair - Kim, Karen (Science and Technology Law Review, 2021)
Many states’ sales and use tax provisions, updated in response to the Supreme Court’s decision in South Dakota v. Wayfair, Inc., will likely impose a disproportionate tax compliance burden on small- and medium-sized businesses (SMBs) that engage in e-commerce. Relative to large companies like Amazon and eBay, SMBs cannot absorb the high compliance costs associated with tracking, collecting, and remitting taxes. Wayfair expanded states’ authority to collect sales taxes on companies without a physical presence in the state. But states should wield this power judiciously. While mimicking South Dakota’s statute (upheld as constitutional in Wayfair) may help states avoid litigation, they would better promote the goals of fairness and efficiency by exempting a larger category of small vendors from sales tax obligations. In light of the COVID‑19 pandemic, which has acutely hurt SMBs, reducing sales tax-related compliance burden would also help states provide relief to struggling SMBs. States should (1) clarify which entities are subject to the remote seller and marketplace facilitator statutes and (2) raise the de minimis safe harbor thresholds that shield smaller businesses from having to remit taxes.